Biosensors: Stimuli‐Responsive Electrodes Detect Oxidative Stress and Liver Injury (Adv. Mater. 8/2015). (February 2015) - Aran, Kiana; Parades, Jacobo; Rafi, Mohammad; Yau, Jennifer F.; Acharya, Abhinav P.; Zibinsky, Mikhail; Liepmann, Dorian; Murthy, Niren
<x xml:space="preserve">Abstract</x> Stimuli‐responsive polymers have a wide range of clinical applications from targeted drug delivery to medical diagnostics. On page 1433, D. Liepmann, N. Murthy, and co‐workers develop a new stimuli‐responsive polymer that is sensitive to reactive oxygen species, and utilize it to develop a point‐of‐care biosensor for measuring oxidative stress and liver injury. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>